Pengaruh Profesionalisme Aparatur dan Kualitas Pelayanan Terhadap Kepuasan Masyarakat di Kantor Kecamatan Bojong Kabupaten Pekalongan Jawa Tengah - Auliya Saputri; Amsar Amsar; Tri Widayati; Aris Mardiyono (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study examines how apparatus professionalism and service quality affect public satisfaction at the Bojong District Office, Pekalongan Regency, Central Java. This study is plagued by the poor Public Satisfaction Index on procedures, requirements, and service duration. This quantitative study uses purposive sampling for 100 Bojong District service customers. SPSS was used to analyse questionnaire data using multiple linear regression. The results of the study show that (1) apparatus professionalism has a positive and significant effect on public satisfaction (t count = 3.056; sig. 0.003), (2) service quality has a positive and significant effect (t count = 6.968; sig. 0.000), and (3) both affect public satisfaction simultaneously (F = 75.584; sig. 0.000) with an adjusted R square value of 60.1%. Public satisfaction is more influenced by service quality than official professionalism. This study emphasises the need to improve official competency and service quality.